Radiative flow past a parabolic started isothermal vertical plate with uniform mass diffusion - Muthucumaraswamy, Rajamanickam; Lakshmi, Velu (Zielona Góra: Uniwersytet Zielonogórski)
A theoretical solution of thermal radiation effects on an unsteady flow past a parabolic starting motion of an infinite isothermal vertical plate with uniform mass diffusion has been studied. The plate temperature as well as the concentration level near the plate are raised uniformly. The dimensionless governing equations are solved using the Laplace-transform technique. The fluid considered here is a gray, absorbing-emitting radiation but a non-scattering medium. The effects of velocity profiles are studied for different physical parameters such as the thermal radiation parameter, thermal Grashof number, mass Grashof number and Schmidt number. It is observed that the velocity increases with increasing values the thermal Grashof number or mass Grashof number. The trend is just reversed with respect to the thermal radiation parameter.
Keywords: parabolic; radiation; isothermal; vertical plate; heat transfer; mass transfer